(3GdQhV GdCfas - (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s
(3ChdgG (B:s
(3EPf Gddg JYGdi dfHjg HGdgLQI PcQ ajg Cf QShd Gddg Udi Gddg Ydjg hSde CJi HjJ CHj HcQ ai GdXgjQI bGdJ YGFTI hai GdHjJ CfG hCNJi s
(3BNQgG (B:s
(3hLRGg YfG CaVd eG jLRi Hg fHjkG Yf CeJg , hdG NGda HfG Yf edJg Efg hdi GdWhd hGdEfYGe , hgh MSHfG hfYe Gdhcjd Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs